Implementasi Kurikulum Merdeka Pendekatan “Deep Learning” dalam Pembelajaran Ilustrasi Digital di SMA - Emil Tegar Salas Efendi; Setyo Yanuartuti; Welly Suryandoko; Indar Sabri (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The Merdeka Curriculum at this time has carried a new approach, namely deep learning that focuses on three principles: full of awareness, meaningful, and encouraging. This paper aims to describe the implementation of the Independent Curriculum with a Deep Learning approach on digital illustration drawing materials at SMA Kemala Bhayangkari 1 Surabaya. The focus of the study is directed to the planning, learning process, and assessment applied by fine arts teachers in grade XII phase F. Writing uses a qualitative method with a case study approach through interview, observation, and documentation techniques. The results of the writing show that teachers have been able to translate the in-depth learning framework that includes the dimensions of graduate profiles, learning principles, learning experiences, and learning frameworks into digital illustration learning activities in a systematic manner. The learning plan is prepared through the determination of the element of "creating", with the selection of materials that are relevant to the needs of the times, and has been integrated with digital media in the form of the Ibis Paint application. The learning process takes place through seven stages ranging from introduction, materials, concept design, sketching, digitization, printing, to reflection. Each stage demonstrates the application of the principles of deep learning: mindful, meaningful, and exhilarating. Assessments are carried out authentically through initial, formative, and summative assessments that emphasize the process and progress of student learning.